Making Basic Learning Modules for Building Construction Class X Competency in Building Modeling and Information Design Skills - Susilawati, Endang; Andreas, Laras Oktavia (CIVED, 2024)
This research was motivated by the problems faced, namely not using modules in the Basic Building Construction Basic Course on Elements of Specifications and Characteristics of Building Materials Based on Green Materials and Construction Work, as well as the competence of Class X Building Information Modeling in Building Modeling and Information Design skills. The purpose of this research is to produce products in the form of valid and practical modules. The research method used is Research &; Development (R&D) and refers to the Decide, Design, Develop and Evaluate (DDD-E) development model. Based on the results of the study, the percentage of material validity test, media validity test, and practicality test was obtained at 76%, 80% and 89.38% respectively. The conclusion in this study is that the learning modules developed are valid and practical to be used in the learning process of the elements of Specifications and Characteristics of Building Materials Based on Green Materials and Construction Works, as well as Building Information Modeling class X Building Modeling and Information Design Competencies.